Oxidation–complexation leaching and kinetic study of rhodium from spent homogeneous catalysts - Yun-ji DING; Jia-yi LI; Huan-dong ZHENG; Yan-jie CUI; Bo LIU; Shen-gen ZHANG (工程科学学报, 2023)
Rhodium-containing homogeneous catalysts are the most active catalysts for homogeneous hydrogenation. Spent homogeneous catalysts contain 100–2000 g∙t–1 of rhodium (Rh) and plenty of hazardous organic components, making them an essential resource of Rh. The recovery of Rh from homogeneous catalysts has excellent economic and environmental benefits. Based on Rh in the spent homogeneous catalysts, a new technology for green dissociation of the Rh–P chemical bond and complexation leaching of Rh was developed, allowing the green and efficient recovery of Rh. Compared with traditional incineration-fragmentation and acid leaching methods, the proposed technology eliminated issues such as long process times, severe environmental pollution, and a low recovery rate of Rh. In this study, first, the low-melting-point organics were removed using distillation. Then, the Rh+ in the homogeneous rhodium–phosphine complex was oxidized as Rh3+ through H2O2, which reduced the binding of organic ligands to Rh. Meanwhile, the RhCl63− formed by Rh3+ and Cl– dissolved into the aqueous solution. The effects of distillation temperature, the concentration of Cl–, the dosage of H2O2, the concentration of H+, and reaction time on the recovery efficiency of Rh were studied. The parameters listed above were optimized using response surface methodology. The results showed that the influence of each parameter on the recovery efficiency of Rh was as follows: H2O2 dosage > Cl– concentration > reaction time. The recovery efficiency of Rh reached 98.22% after 4 h of distillation at 260 °C, leaching Rh in the mixture solution of 3.0 mol∙L–1 Cl–, 37% (volume fraction) of the spent homogeneous catalyst dosage of H2O2, 1.0 mol∙L–1 H+, and at 90 °C for 4.5 h. Finally, the oxidation–complexation kinetic behavior of Rh was studied using spectrophotometry. The activation energy of the leaching reaction was 39.24 kJ∙mol–1, indicating that the rate-controlling step of this process was a surface chemical reaction.